Time to look east: Lessons from revisiting Asian economic integration - Upalat Korwatanasakul (Asian Development Bank Institute (ADBI), 2020)
Covering major Asian economic blocs and dialogues, this study comprehensively reviews the true progress of "Asian" economic integration in comparison with the European Union (EU) and examines the factors contributing to the integration. The results show that comprehensive continent-wide economic integration in Asia is unlikely to happen soon, since the integration is confined mainly to East and Southeast Asia, while other regions are much less integrated and globalized. The Association of Southeast Asian Nations and the Regional Comprehensive Economic Partnership perform well in terms of trade and market integration and show high potential in leading other economic blocs in the region. The results also suggest that gradual integration and expansion would help intensify Asian economic integration through capacity-building and technological development from more advanced economic blocs. This would help the less developed blocs to integrate smoothly with the others. This study also argues that the factors or attributes proposed in the previous literature-among others, pooled sovereignty; historical reconciliation; common institutions; and heterogeneity in economic, political, and social factors-are irrelevant in the context of Asian economic integration. Instead, the scope, depth, and sequencing of the integration process largely explain the success of the Asia model. Unlike the experience of the EU, the model is heavily market-driven and private-sector oriented due to the impact of globalization and changes in global trade patterns and production process, such as fragmented trade and production, and regional production. Government and institutional mechanisms are relatively unimportant in the Asia model.
Keywords: F10; F15; F50; F55; 330; Asian economic integration; economic integration; regional integration; intraregional trade; European Union; integration policy